Neuronal Glycoprotein M6a: An Emerging Molecule in Chemical Synapse Formation and Dysfunction - León, Antonella; Aparicio, Gabriela I.; Scorticati, Camila (Frontiers in Synaptic Neuroscience, 2021)
The cellular and molecular mechanisms underlying neuropsychiatric and neurodevelopmental disorders show that most of them can be categorized as synaptopathies -or damage of synaptic function and plasticity. Synaptic formation and maintenance are orchestrated by protein complexes that are in turn regulated in space and time during neuronal development allowing synaptic plasticity. However, the exact mechanisms by which these processes are managed remain unknown. Large-scale genomic and proteomic projects led to the discovery of new molecules and their associated variants as disease risk factors. Neuronal glycoprotein M6a, encoded by the GPM6A gene is emerging as one of these molecules. M6a has been involved in neuron development and synapse formation and plasticity, and was also recently proposed as a gene-target in various neuropsychiatric disorders where it could also be used as a biomarker. In this review, we provide an overview of the structure and molecular mechanisms by which glycoprotein M6a participates in synapse formation and maintenance. We also review evidence collected from patients carrying mutations in the GPM6A gene; animal models, and in vitro studies that together emphasize the relevance of M6a, particularly in synapses and in neurological conditions.